Moral Education in Buya Hamka’s Tafsir Al-Azhar: Qur’anic Values and Contemporary Islamic Pedagogy - Auliansyah Raja Hamonangan Hutasuhut (Jurnal Pendidikan Islam, 2026)
This study analyzes Buya Hamka’s concept of moral education in Tafsir Al-Azhar and identifies the Qur’anic moral values embedded in his interpretation. It employs a descriptive qualitative design through library research and tafsir-based textual analysis. The primary source is Tafsir Al-Azhar, supported by Hamka’s other works and relevant studies on Islamic education, moral education, and Indonesian Qur’anic exegesis. Data were collected through documentation and analyzed using qualitative content analysis through coding, categorization, and thematic synthesis. The findings show that Hamka’s moral education is grounded in the integration of faith, knowledge, and righteous action. It forms three domains of moral responsibility: morality toward God, morality toward oneself, and morality toward fellow human beings. These domains are developed through exemplary conduct, habituation, advice, spiritual supervision, purification of the soul, and rational reflection. The study concludes that Hamka’s moral education offers a contextual Qur’anic framework for contemporary Islamic pedagogy by linking personal piety, family-based formation, social responsibility, and digital moral literacy.